Associations between obesity and ocular health in Spanish adults. Issue 1 (14th September 2020) - Jacob, Louis; Smith, Lee; Koyanagi, Ai; Pardhan, Shahina; Allen, Peter; Yang, Lin; Grabovac, Igor; Shin, Jae Il; Tully, Mark A.; López‐Sánchez, Guillermo F.
Abstract: Introduction: Obesity has been associated with poor vascular health, but not in a Spanish population. Therefore, the study aimed to investigate associations between obesity and cataract, wearing glasses or contact lenses, and trouble seeing in a large representative sample of the Spanish adult population. Methods: Cross‐sectional data from the Spanish National Health Survey 2017 were analyzed. Body mass index (BMI) was calculated and obesity was defined as BMI ≥ 30 kg/m 2 . Ocular health included three dichotomous variables (presence vs absence): self‐reported cataract, wearing glasses or contact lenses, and trouble seeing. Multivariable logistic regressions were used to assess associations between obesity (independent variable) and ocular health outcomes (dependent variables). Covariates included in the analysis were sex, age, marital status, education, smoking, alcohol, and diabetes. Results: A total of 23 089 participants were included (54.1% female; mean [SD] age = 53.4 [18.9] years). After adjusting for sex, age, marital status, education, smoking, alcohol, diabetes, and wearing glasses or contact lenses (for the trouble seeing analysis only), obesity was found to be a risk factor for cataract (odds ratio [OR] = 1.22; 95% confidence interval [CI], 1.09‐1.37) and trouble seeing (OR = 1.20; 95% CI, 1.09‐1.32) but not for wearing glasses or contact lenses (OR = 0.99; 95% CI, 0.91‐1.08). These findings were corroborated in participants ≥64 years. Conclusions: In this large representative sample of Spanish adults, we found that obesity was a risk factor for cataract and trouble seeing. Lifestyle interventions aiming at the reduction of obesity in this population may indirectly improve ocular health. Such lifestyle interventions are important to implement considering the rising trend of obesity in Spain.